The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1063/1.4944470
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic effects in molecular transport junctions: The probe technique at high bias

Abstract: We extend the Landauer-Büttiker probe formalism for conductances to the high bias regime, and study the effects of environmentally-induced elastic and inelastic scattering on charge current in single molecule junctions, focusing on high-bias effects. The probe technique phenomenologically incorporates incoherent elastic and inelastic effects to the fully coherent case, mimicking a rich physical environment at trivial cost. We further identify environmentally-induced mechanisms which generate an asymmetry in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 76 publications
1
39
0
Order By: Relevance
“…Here, we use an alternative, low-cost technique and account for system-environment interactions by employing the Landauer-Büttiker probe method [27,28]. It is applicable for the study of charge conduction in a wide range of systems, from single-atom point contacts up to the thermodynamic limit [19,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]65]. In this technique, incoherent elastic and inelastic electron (or hole) scattering effects are taken into account by augmenting the non-interacting electronic Hamiltonian with probe terminals through which charge carriers loose their phase memory and possibly exchange energy with other degrees of freedom.…”
Section: Nuclear Environmentmentioning
confidence: 99%
“…Here, we use an alternative, low-cost technique and account for system-environment interactions by employing the Landauer-Büttiker probe method [27,28]. It is applicable for the study of charge conduction in a wide range of systems, from single-atom point contacts up to the thermodynamic limit [19,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]65]. In this technique, incoherent elastic and inelastic electron (or hole) scattering effects are taken into account by augmenting the non-interacting electronic Hamiltonian with probe terminals through which charge carriers loose their phase memory and possibly exchange energy with other degrees of freedom.…”
Section: Nuclear Environmentmentioning
confidence: 99%
“…In Refs. 41,42 , we further used the LBP technique to simulate high-bias voltage effects, specifically, the role of environmental interactions on the operation of a molecular junction as a diode.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. 58,59 , we further used the LBP technique to simulate high-bias voltage effects, specifically the role of environmental interactions on the diode operation. More recently, we demonstrated that the LBP method can uncover an intermediate quantum coherent-incoherent transport regime in DNA junctions 60 .…”
Section: Introductionmentioning
confidence: 99%